Home Made Four-Point Probe: Case Studies of the Wobbly A and B Probes - Toifur, Moh.; Sukarelawan, Moh. Irma; Okimustava, Okimustava (Universitas Ahmad Dahlan, 2023)
A simulation on the effect of probe deviation on sheet resistivity value (Rs) of Cu/Ni thin film was carried out in a home-made four-point probe (HM-FPP) type. This began by solving the Rs formula for normal probes, and then for wobbly probe when it was either A, or both A and B. The formula was implemented on a thin layer of Cu/Ni, which was a low temperature sensor material obtained from electrodeposition for 60s assisted by a 200G magnetic field at a current density of 0.07A/mm2. An electric current of 0.20118A was flown from probe A to D in order to produce a potential difference between probe C and D of 0.0005 volts. Furthermore, the distance between the probes was 5 mm and the deviation of each probe A and B were simulated from -0.5 mm to 0.5 mm. The maximum allowable limit for the relative error of Rs or SRs is 5%. The results showed that the ideal Rs value was 0.113 ohm/sq. Furthermore, for HM-FPP in which the wobbly probe only A, there is no problem encountered with the variation of the deviation because all SRs are less than 5%. For wobbly probes A and B, if they are on the same side of the center point of each probe, the maximum allowable deviation is 0.3 mm. The SRs for this case were 4.6%. However, if they are on different sides of the center point of each probe, the maximum allowable deviation is 0.1 mm with SRs of 2.9%. With these results, HM-FPP craftsmen must be more careful in making the size of the probe hole.